Jan Surman. Universities in Imperial Austria, 1848–1918. A Social History of a Multilingual Space - Stan, Ana-Maria (CIAN-Revista de Historia de las Universidades, 2020)
This article review:  Jan Surman. Universities in Imperial Austria, 1848–1918. A Social History of a Multilingual Space. Indiana: Purdue University Press, 2019, 458 pp.